1998
DOI: 10.1021/la980489y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ion Size on Short-Range Repulsive Forces between Silica Surfaces

Abstract: The influence of counterion size on short-range repulsive forces at high salt concentrations was investigated with silica slurries at various pHs. Ions from the lyotropic series of monovalent electrolytes (LiCl, NaCl, KCl, and CsCl) were used to coagulate dispersed slurries. Measurements of viscosity and sedimentation rate were performed. The results at high salt concentrations and volume fractions of silica clearly show that the extent of the short-range repulsive forces correlates with the size of the unhydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
74
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 35 publications
14
74
1
Order By: Relevance
“…The adhesion dependence on the cation species is correlated excellently with the recent rheological studies performed with silica and aluminum slurries by Colic, and Franks and co-authors (4)(5)(6)(7)(8). They have shown that the strength of attractive particle networks in the high electrolyte concentration solutions decreases in the sequence: Li + > Na + > K + > Cs + .…”
Section: Fig 14supporting
confidence: 83%
“…The adhesion dependence on the cation species is correlated excellently with the recent rheological studies performed with silica and aluminum slurries by Colic, and Franks and co-authors (4)(5)(6)(7)(8). They have shown that the strength of attractive particle networks in the high electrolyte concentration solutions decreases in the sequence: Li + > Na + > K + > Cs + .…”
Section: Fig 14supporting
confidence: 83%
“…There are the other reports claiming that the repulsive force between silica surfaces is explained by the hydration of surfaces rather than by a gel layer (8,9). The existence of a thick structured layer is also suggested by coagulation experiments with silica dispersions (24) and rheological studies on silica and aluminum slurries (25)(26)(27).…”
Section: Discussionmentioning
confidence: 95%
“…However, in silica and glass systems the additional force does not seem to be strongly dependent on the type or concentration of electrolyte. In fact, a decrease in magnitude of the non-DLVO forces with increasing electrolyte concentration has been reported (2,3,21). As a result of these investigations, it is generally assumed that the origin of the non-DLVO forces on silica is different than those in other oxide systems.…”
Section: Long-range Interaction Forcesmentioning
confidence: 99%